Where did all the Hunters go? : An Assessment of an Epoch-Making Episode in Danish Prehistory - Madsen, Thorsten (Journal of Danish Archaeology, 1986)
Where did all the Hunters go? An Assessment of an Epoch-Making Episode in Danish Prehistory